Reformulating Marriage Registration Law in Indonesia: A Review of Article 2(2) of the 1974 Marriage Law - Rizal Arif Fitria; M. Fahmi Al-Amruzi; Akhmad Sukris Sarmadi (The Indonesian Journal of Islamic Law and Civil Law, 2026)
Marriage registration constitutes a fundamental instrument within Indonesia’s family law system to ensure legal certainty, protection of civil rights, and administrative order. However, Article 2 paragraph (2) of Law Number 1 of 1974 on Marriage continues to give rise to normative and practical problems due to its ambiguous relationship with paragraph (1), which emphasizes the validity of marriage based on religious law. This ambiguity has produced a dualistic interpretation of marriage registration, which is often perceived merely as an administrative obligation lacking strong legal binding force. Consequently, the practice of unregistered marriages (nikah siri) persists and systematically weakens legal protection, particularly for women and children. This study employs a normative legal approach supported by empirical data in the form of statistical records of itsbat nikah applications submitted to the Religious Courts, sourced from the Directorate General of the Religious Courts of the Supreme Court of the Republic of Indonesia. The analysis is conducted using the perspectives of legal positivism, structural functionalism, law as a tool of social engineering, and maqasid al-shari‘ah (maslahah). The findings indicate that the high number of itsbat nikah applications reflects the inability of marriage registration norms to function effectively as instruments of legal protection.